Biomechanical characteristics of grinding in America`s cup sailing - Pearson, S.; Hume, P.; Cronin, J.; Slyfield, D. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Understanding the biomechanics of a sporting movement and what aspects of the movement technique most influence performance can facilitate more specific training, both in terms of strength and conditioning and technical improvements. This study was undertaken to describe the kinetic, kinematic, and muscular activation characteristics of the grinding movement in America`s Cup sailing, a high intensity constrained cyclic movement (similar to bicycling) performed with the upper limbs.